Single vs Two Stage Solution: Outcomes of Primary Anastomosis After Uncomplicated Sigmoid Volvulus (Faridpur Medical College Journal, 2026)
Background: Sigmoid volvulus is a life-threatening cause of large bowel obstruction, and debate continues over whether single-stage or two-stage surgery is safer and more effective. This study directly compares both approaches in uncomplicated cases to help guide optimal surgical decisions.Methods: This interventional study, conducted at Shaheed Ziaur Rahman Medical College Hospital from October 2018 to April 2019, enrolled fifty consecutive patients diagnosed with uncomplicated sigmoid volvulus, while patients presenting with shock, severe comorbidities, bowel gangrene, discontinuation of treatment, or unwillingness to provide consent were excluded from participation. After careful clinical evaluation and admission for surgical management, all eligible patients were divided into two groups according to the operating surgeon’s preference and intraoperative judgment. In one group, a single-stage procedure with resection and primary anastomosis was performed, whereas the second group underwent a planned two-stage surgical approach. Each group consisted of 25 patients, allowing a balanced comparison between the two operative strategies.Result: Both one-stage and two-stage groups were similar in age (49.4 ± 19.1 vs 50.9 ± 13.9), sex (male 84% vs 80%), diabetes (28% vs 20%), and hypertension (20% vs 28%), with no significant differences in vital signs. Operative time (92.4 ± 19.2 vs 71.6 ± 11.8 min, p